Fast-Sec: an approach to secure Big Data processing in the cloud. Issue 3 (4th May 2019) - Anjos, Julio C. S. dos; Galibus, Tatiana; Geyer, Cláudio F. R.; Fedak, Gilles; Costa, João Paulo C. L.; Pereira, Rubem; de Freitas, Edison Pignaton
ABSTRACT: Security is an important concern in computer systems, which is especially remarkable when the system has to handle large amounts of data and some different users accessing this data with different accessing permissions. This work proposes an innovative approach for providing a security infrastructure support to Big Data Analytic in Cloud-based systems named Fast-sec. Fast-Sec handles systems with large volumes of data from heterogeneous sources, in which users may access the system by different platforms, consuming or providing data. The security infrastructure proposed in Fast-Sec provides an authentication mechanism for users, and data access control adapted to high demands from cloud-based Big Data environment. The reported results show the adequacy of the proposed safety infrastructure to the cloud-based systems processing Big Data. Graphical Abstract: Fast-Sec: An Approach to Secure Big Data Processing in the Cloud.